2014
DOI: 10.1097/ccm.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Blood Gas Tensions After Resuscitation From Out-of-Hospital Cardiac Arrest

Abstract: In this multicenter study, hypercapnia was associated with good 12-month outcome in patients resuscitated from out-of-hospital cardiac arrest. We were unable to verify any harm from hyperoxia exposure. Further trials should focus on whether moderate hypercapnia during postcardiac arrest care improves outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
119
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 34 publications
3
119
1
3
Order By: Relevance
“…13,16,18,21,37 In our study, lower PaO2 values and higher oxygen needs established in terms of PaO 2 /FiO 2 rates, were found in patients with poor neurological long-term outcome, in accordance to results previously published by Vaahersalo in an adult population. 38 In contrast to their findings, carbon dioxide values were not found to influence neurologic longterm outcome in our patients, but if any, PCO 2 higher than 50 mmHg both at 1 h and 24 h after ROSC, showed a trend towards worsening neurological outcome rather than favoring it, which was observed too by Roberts et al 39 Hyperoxia was not found to be associated with a poorer neurological outcome.…”
Section: Post-resuscitation Variablescontrasting
confidence: 75%
“…13,16,18,21,37 In our study, lower PaO2 values and higher oxygen needs established in terms of PaO 2 /FiO 2 rates, were found in patients with poor neurological long-term outcome, in accordance to results previously published by Vaahersalo in an adult population. 38 In contrast to their findings, carbon dioxide values were not found to influence neurologic longterm outcome in our patients, but if any, PCO 2 higher than 50 mmHg both at 1 h and 24 h after ROSC, showed a trend towards worsening neurological outcome rather than favoring it, which was observed too by Roberts et al 39 Hyperoxia was not found to be associated with a poorer neurological outcome.…”
Section: Post-resuscitation Variablescontrasting
confidence: 75%
“…One study 187 with a total of 850 patients showed no difference in outcome for patients ventilated to hypercapnia (Paco 2 greater than 6.0 kPa). One study 178 with a total of 409 patients showed better outcome for patients ventilated to hypercapnia (Paco 2 5.1-10.1 kPa).…”
Section: Hypercapniamentioning
confidence: 99%
“…For the critical outcome of survival to 12 months with favorable neurologic outcome (CPC 1 or 2), 1 study 178 of verylow-quality evidence (downgraded for very serious risk of bias and indirectness) showed no harmful effect associated with hyperoxia during the first 24 hours of ICU care.…”
Section: Hyperoxia Versus Normoxiamentioning
confidence: 99%
“…Over recent years, this dogma has started to be questioned in light of emerging, though somewhat equivocal, evidence from both animal models [2] and retrospective analyses of cardiac arrest registries [3] which suggest an association between the degree and cumulative exposure to hyperoxia, and both short-term mortality and worse neurological outcomes in survivors. Crucially, hyperoxia is frequently accompanied by hyperventilation with consequent and injurious, hypocapnia [4,5]. Thus, there is biological plausibility for the concept that cardiac arrest and current resuscitation practice subjects patients to a two-hit injury model made worse by hyperoxia (Table 1).…”
mentioning
confidence: 99%
“…Data regarding well-established factors that affect the outcome variables chosen are not presented. These include: pre-arrest co-morbidities [8]; the cause of the cardiac arrest (specifically cardiogenic verses noncardiogenic, though initial cardiac rhythm is accounted for and can be considered as a surrogate for this variable); the time from cardiac arrest to first effective CPR and the duration of CPR (time from arrest to RoSC) [9,10]; the cumulative dose of epinephrine (higher cumulative doses are associated with worse neurological outcome [11]); arterial carbon dioxide data [4,5]; and the proportion of patients who underwent emergency coronary angiography, with or without intervention [12].…”
mentioning
confidence: 99%